Mampukah Model Enam Faktor Fama and French menggungguli Model Tiga Faktor Fama and French dengan Proksi Indeks Kompas 100 - Dasril, Yuki Dwi Darma; Indriati, Petiana; Pujiharta, Pujiharta; Hartati, Nani; Indriani, Meika (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
accompanying risks, many researchers have attempted to find financial asset valuation models. One of the most popular ones today is the Fama and French model. The initial model introduced was the Fama and French 3-factor model, which encountered various failures in some emerging market capital markets. In response, Fama and French improved their model, transforming it into a 6-factor model by adding aspects of profitability, investment, and momentum. This adjustment aimed to capture the relationship between the returns of securities or portfolios formed with systematic risk. However, the Fama and French 6-factor model did not perform well in some emerging market capital markets. The objective of this research is to test the accuracy of the Fama and French 6-factor model in the Indonesian Capital Market from 2017 to 2021. The research method employed is multiple linear regression, forming portfolios based on the framework established by the Fama and French 6-factor model. The research findings indicate evidence that the Fama and French 6-factor model can explain the returns of the formed portfolios. Market risk, book-to-market ratio, and investment aspect significantly impact the performance of the formed portfolio returns.